Deformed Mediated Larval Incisor Lobe Development Causes Differing Feeding Behavior between Oriental Armyworm and Fall Armyworm - Hailong Zhao; Zeng Zhu; Gaoliang Xing; Yiyu Li; Xue Zhou; Jingjing Wang; Guiting Li; Haiqun Cao; Yong Huang (Insects, 2022)
Mandibular incisor lobes are important for insect feeding behavior, living habits and niche. However, the molecular regulation of insect incisor lobe development remains unknown. In this study, we found that two maize pests, oriental armyworm Mythimna separata and fall armyworm Spodoptera frugiperda, have different feeding patterns in maize, which are closely associated with the different development patterns of their incisor lobes. Different from first to sixth instar S. frugiperda, which feed on leaf tissues and whorls with sharp incisor lobes, older instars of M. separata feed from leaf margins with no incisor lobes. Hox gene Deformed (Dfd) is important for head appendages, but its function in incisor lobe development is not clear. Here, Dfds were identified from two armyworm species, and both were expressed highly in heads and eggs. Interestingly, the expression levels of MsDfd were relatively high in larval mandibles and decreased dramatically from fourth-instar mandibles in M. separata. Knockdown of MsDfd resulted in malformed mandibles with no incisor lobe in M. separata, making the larvae unable to perform window-feeding. However, RNAi of SfDfd did not affect the mandibles and window-feeding pattern of S. frugiperda, indicating the different roles of Dfd in these two species. Moreover, the mortality of new first instar M. separata increased after feeding dsMsDfd but did not for S. frugiperda feeding dsSfDfd. These findings revealed that Dfd mediated the larval mandibular incisor lobe morphology, affecting its feeding pattern in M. separata, broadening the knowledge of Dfd functions in insect mandibles and feeding behavior.